Rahmatan Lil ‘Alamin Dalam Dunia Perbankan: Service Excellence Dalam Pandangan Islam - Syahdara Anisa Makruf (Jurnal Multidisiplin Indonesia, 2025)
Muslims, the majority of Indonesia's population, have not yet adopted Islamic banking as a preferred financial transaction service. One important consideration is service excellence. Service excellence is one effective way to attract customers. However, there has been no detailed discussion of the Islamic perspective on service excellence. This paper will focus on a detailed examination of the Islamic perspective on service excellence based on the texts of the Quran and Hadith. Using a qualitative approach, data collection through documentation and literature studies is conducted. This study found that the basic principles of excellent service are more appropriately aligned with the Islamic da'wah method. This Islamic da'wah method focuses on three main aspects: Al-Hikmah (Wisdom), Al-Mauidzah bil Hasanah (Prosperity), and Mujadalah bil Hasanah (Prosperity). This paper also found that every employee should have this service excellence based on the principles of the Prophet Muhammad: siddiq (Integrity), amanah (Trust), tabligh (Prosperity), and fathonah (Integrity). These four points are absolutely essential because they represent the ideal model for every employee.